2021
DOI: 10.33448/rsd-v10i3.13071
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and regional gastronomy: cassava leaves as a potential ingredient for gluten-free biscuits

Abstract: The addition of roots derivatives to bakery products may be a promising alternative to add value to these products. This study aimed to characterize and evaluate the effect of cassava leaves on the properties of gluten-free biscuits (GFB). The ingredients used were cassava flour, rice flour, cuí, tapioca flour, and 0 (F0), 3.69% (F1), 5.34% (F2), and 7.38% (F3) of cassava leaves (CCL). The results were evaluated by analysis of variance, followed by Scott-Knott test (p-value<0.05). The CCL presented 89.9% mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Low water activity levels (0.33 to 0.50) were detected for all processing parameters. The water activity of cassava leave flour in this study (0.33 to 0.50) was close to that reported by [7], who reported that, the water activity of cassava leaf flour was between 0.38 and 0.43. This suggests that cassava leaves flour may have the best storage stability in relation to water activity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Low water activity levels (0.33 to 0.50) were detected for all processing parameters. The water activity of cassava leave flour in this study (0.33 to 0.50) was close to that reported by [7], who reported that, the water activity of cassava leaf flour was between 0.38 and 0.43. This suggests that cassava leaves flour may have the best storage stability in relation to water activity.…”
Section: Resultssupporting
confidence: 90%
“…Several crops are underutilized in the majority of areas where they are grown due to a lack of awareness about their complete nutritional and anti-nutrition values, as well as information on processing. Growing drought-resistant crop varieties and employing appropriate food processing methods and equipment may help to reduce the dangers to one's health [7]. However, the level of cyanide in the cassava can be effectively reduced with different processing methods.…”
Section: Introductionmentioning
confidence: 99%
“…The production of olive oil in Brazil contributes to widespread consumption, a factor of great nutritional interest. In this way, the elaboration of products from olive oil and extraction byproducts such as olive pomace can contribute to the diversification of the economy in the producing centers, increasing the offer of products with added value, diversifying the forms of consumption, and increasing the consumption of olive oil in the Brazilian population (Neves et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The use of ingredients rich in bioactive compounds can be an alternative for the nutritional improvement of foods (Neves et al, 2021;Vilar et al, 2021;Wahanik et al, 2021). Besides the economic value added, the use of roots and tubers in instant noodles may contribute to enrich the population diet by the increase of bioactive compounds in this product, such as with antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%